Compact NMR relaxometry of human blood and blood components - Cistola, David; Robinson, Michelle D. (My University, 2016)
Nuclear magnetic resonance relaxometry is a uniquely practical and versatile implementation of NMR technology. Because it does not depend on chemical shift resolution, it can be performed using low- field compact instruments deployed in atypical settings. Early relaxometry studies of human blood were focused on developing a diagnostic test for cancer. Those efforts were misplaced, as the measurements were not specific to cancer. However, important lessons were learned about the factors that drive the water longitudinal (T1) and transverse (T2) relaxation times. One key factor is the overall distribution of proteins and lipoproteins. Plasma water T2 can detect shifts in the blood proteome resulting from in- flammation, insulin resistance and dyslipidemia. In whole blood, T2 is sensitive to hemoglobin content and oxygenation, although the latter can be suppressed by manipulating the static and applied magnet- ic fields. Current applications of compact NMR relaxometry include blood tests for candidiasis, hemostasis, malaria and insulin resistance.